2016
DOI: 10.2105/ajph.2015.302875
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Framework of Legalized Marijuana in Colorado

Abstract: On January 1, 2014, Colorado became the first state in the nation to sell legal recreational marijuana for adult use. As a result, Colorado has had to carefully examine potential population health and safety impacts as well as the role of public health in response to legalization. We have discussed an emerging public health framework for legalized recreational marijuana. We have outlined this framework according to the core public health functions of assessment, policy development, and assurance. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 17 publications
0
33
0
4
Order By: Relevance
“…In addition internet pop-up advertisements are prohibited. (Ghosh et al,2015). However there are exceptions.…”
Section: March 22)mentioning
confidence: 99%
“…In addition internet pop-up advertisements are prohibited. (Ghosh et al,2015). However there are exceptions.…”
Section: March 22)mentioning
confidence: 99%
“…1 This distribution model has come with an increased availability of marijuana-infused edibles, such as cookies, brownies, or candy. 2 Studies have observed higher consumption of marijuana-infused edibles in states permitting medical and/or recreational marijuana use when compared to states not permitting this use. 34 …”
Section: Introductionmentioning
confidence: 99%
“…Thus users may take more in an attempt to feel high more quickly, increasing the likelihood of erratic behaviors associated with adverse psychological effects arising from overconsumption. 2 Second, accidental ingestion by and poisonings of young children may occur because edibles often look like candy or baked goods. 5 These products are also attractive to adolescents as it makes it easier to conceal use.…”
Section: Introductionmentioning
confidence: 99%
“…Celui-ci regrettant l'autorisation donnée par l'État à la production de cannabis « comestible » (edibles) (source : Cannalex). Il s'avère aujourd'hui que la consommation de cannabis comestible constitue une part majeure dans la croissance importante des admissions aux urgences hospitalières de l'État consécutives à l'usage de cannabis (Ghosh, 2016 ;Kim, 2016). avec environ 11,2 millions de dollars pour le secteur « récréationnel » et 2 millions de dollars pour le secteur « médical ».…”
Section: Légalisation « Contrôlée » Vs Légalisation « Libérale »unclassified
“…À la suite de cette décision judiciaire, le nombre de dispensaires agréés (licensed dispensaries) passe en quelques années de 250 à 532 et le nombre d'usagers de marijuana médicale de 4 000 à plus de 115 000 (Ghosh, 2015) [25] . Il serait cependant caricatural de réduire le modèle du Colorado à sa seule dimension économique libérale (Ghosh et al, 2016). Un certain nombre de régulations publiques ont été mises en place, puis renforcées après quelques mois d'application de la réforme.…”
unclassified